Temperature control of shoot growth and floral initiation in apple (Malus × domestica Borkh.) - Heide, Ola M.; Rivero, Rodmar; Sønsteby, Anita (CABI agriculture and bioscience, 2020)
Background The environmental control of flowering in apple (Malus × domestica Borkh.) has remained an enigma for generations. Methods We studied growth and flowering effects of temperature under daylight phytotron conditions in 3-year old ‘Summerred’ and ‘Discovery’ apple trees. Flowering was assessed by dissection of buds on spurs and extension shoots at termination of treatments and flowering performance in the subsequent spring. Results Exposure to constant temperatures ranging from 12 to 27 °C for 12 weeks yielded a hyperbolic response curve with optimum at 18–21 °C and little or no flowering at 12 and 27 °C. A drop from high to low temperature after 6 weeks caused growth cessation and initiation of flowering, whereas the reverse shift had the opposite effect. Shoot growth and leaf accumulation increased with increasing temperature, but under flower-inducing conditions, both levelled off and ceased towards the end of the treatment period. Conclusions The results are discussed in relation to the extensive physiological and genetic literature on the subject. We interpret the results as two separate effects of temperature on flowering in apple. At 12 °C flowering seems to be limited by low temperature depression of growth and leaf production, while at 27 °C, flowering is blocked by inhibition of the floral initiation itself. Intermediate temperatures of 18–21 °C, on the other hand, seem to satisfy the requirements for both processes. These opposite effects of temperature have apparently confounded the understanding of the environmental control of flowering in apple.